Short fatigue crack initiation and growth modeling in aluminum 7075-T6. (May 2015) - Amiri, M; Modarres, M
A series of fatigue tests is carried out to investigate the behavior of microcrack initiation and propagation in Al 7075-T6. Plate specimens with semi-circular single edge notch are tested under uniaxial loading at different load amplitudes. Optical microscopy is used to detect the initiation and growth of short cracks. Continuum damage mechanics is used to model the crack initiation. After the initiation, crack growth is studied using fracture mechanics models. For both regions of crack initiation and growth, Bayesian estimation method is used to account for uncertainties in the parameters of the model. Results of the entire fatigue life, including initiation and growth, are compared with experiments. Good agreement is observed.